Dependency on imported agricultural inputs : global trade patterns and recent trends - Sandström, Vilma; Huan-Niemi, Ellen; Niemi, Jyrki; Kummu, Matti (IOP Publishing, 2024)
Industrial food production systems depend on inputs such as fertilisers, pesticides, and commercial animal feeds that are highly traded commodities in global markets. Disturbances in international trade can threaten the local food production if the imports of the key agricultural inputs were drastically reduced. However, despite the importance of the topic, a comprehensive analysis focusing on the import dependency of multiple agricultural inputs at the global level and thus revealing the vulnerability of regions and individual countries does not exist. Here, we analyse the temporal trends of agricultural input trade globally at the national scale from 1991 to 2020 by applying statistics of the use and trade of synthetic fertilisers (N, P, and K), pesticides and livestock and aquaculture feeds (grouped into oilseed feeds and other feed crops). The results show that the import dependency of agricultural inputs has increased over the past 30 years, but there is high variation between countries. Countries with high import dependency combined with high use of these inputs, such as many industrial agricultural producers in South America, Asia as well as Europe, show high vulnerability to trade shocks. Also, our findings highlight that potential agricultural intensification in Sub-Saharan African countries—currently with low use of the inputs per cropland area but high import dependency—can lead to higher dependency on imported agricultural inputs. Therefore, understanding of the past trends and current risks associated with the dependency on imported agricultural inputs should be highlighted to mitigate the risks and build more resilient and sustainable food systems.
Keywords: agricultural inputs; international trade; fertilisers; pesticides; animal feed